Glutamate Metabolism is Impaired in Transgenic Mice with Tau Hyperphosphorylation. Issue 5 (May 2013) - Nilsen, Linn Hege; Rae, Caroline; Ittner, Lars M; Götz, Jürgen; Sonnewald, Ursula
In neurodegenerative diseases including Alzheimer's disease and frontotemporal dementia, the protein tau is hyperphosphorylated and eventually aggregates to develop neurofibrillary tangles. Here, the consequences of tau hyperphosphorylation on both neuronal and astrocytic metabolism and amino-acid neurotransmitter homeostasis were assessed in transgenic mice expressing the pathogenic mutation P301L in the human tau gene (pR5 mice) compared with nontransgenic littermate controls. Mice were injected with the neuronal and astrocytic substrate [1- 13 C]glucose and the astrocytic substrate [1, 2- 13 C]acetate. Hippocampus and cerebral cortex extracts were analyzed using 1 H and 13 C nuclear magnetic resonance spectroscopy, gas chromatography–mass spectrometry and high-performance liquid chromatography. The glutamate level was reduced in the hippocampus of pR5 mice, accompanied by reduced incorporation of 13 C label derived from [1- 13 C]glucose in glutamate. In the cerebral cortex, glucose utilization as well as turnover of glutamate, glutamine, and GABA, were increased. This was accompanied by a relative increase in production of glutamate via the pyruvate carboxylation pathway in cortex. Overall, we revealed that astrocytes as well as glutamatergic and GABAergic neurons in the cortex of pR5 mice were in a hypermetabolic state, whereas in the hippocampus, where expression levels of mutant human tau are the highest, glutamate homeostasis was impaired.